2007
DOI: 10.1177/1933719107307908
|View full text |Cite
|
Sign up to set email alerts
|

The Regulation of Adrenocorticotrophic Hormone Receptor by Corticotropin-Releasing Hormone in Human Fetal Adrenal Definitive/Transitional Zone Cells

Abstract: As gestation progresses, human fetal adrenals (HFA) initiate the production of cortisol, which increases placental corticotropin-releasing hormone (CRH) biosynthesis. While adrenocorticotrophic hormone (ACTH) is important for the onset of cortisol production, the late gestational surge in cortisol production occurs despite falling ACTH levels in the fetal circulation. The authors determine if CRH directly regulates the expression of the ACTH receptor (ACTHR) in HFA definitive/transitional zone (DZ/TZ) cells. D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 49 publications
1
21
0
Order By: Relevance
“…In agreement with previous studies (Le Roy et al 2000; Rehman et al 2007; Carey et al 2006; Su et al 2005; Johnston et al 2007; Mountjoy et al 1994), we found that the ACTH receptor-MC2R was significantly stimulated by ACTH incubation (12-fold). We also noticed a significant increase in MRAP mRNA level.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In agreement with previous studies (Le Roy et al 2000; Rehman et al 2007; Carey et al 2006; Su et al 2005; Johnston et al 2007; Mountjoy et al 1994), we found that the ACTH receptor-MC2R was significantly stimulated by ACTH incubation (12-fold). We also noticed a significant increase in MRAP mRNA level.…”
Section: Discussionsupporting
confidence: 93%
“…For experiments AA or FA cells were subcultured and plated at a density of 200,000/ well in 24 well dishes and allowed to grow for 5 days in complete growth medium [10% Cosmic calf serum (Hyclone), 1% antibiotic, for adult adrenal cells] (Bassett et al 2004) [10% Cosmic calf serum, 1% ITS plus (BD Diagnostic Systems, Sparks, MD) and 1% antibiotic for fetal adrenal cells] (Rehman et al 2007). The day before treatment, the cells were changed to experimental medium (0.1% Cosmic calf serum, 1% antibiotics for adult adrenal cells and 1% cosmic calf serum, 1% ITS plus, 1% antibiotic for fetal adrenal cells) for overnight incubation and then treated for an indicated time either under basal conditions or with ACTH (10 nM) (Organon, Bedford, OH).…”
Section: Methodsmentioning
confidence: 99%
“…Interestingly, many adverse intrauterine conditions that have been associated with impaired fetal brain development also have been associated with a down-regulation of placental 11β-HSD2 activity, including high maternal anxiety (42), severe infection (43), high levels of proinflammatory cytokines (44), and alcohol exposure (45). Another plausible pathway by which maternal cortisol can produce elevations in fetal cortisol level is by stimulating and thereby increasing the production of placental corticotrophin-releasing hormone (46)(47)(48), which is known to act on the fetal HPA axis and stimulate adrenal steroid biosynthesis. Finally, a small number of human studies that have obtained paired maternal and fetal plasma samples during gestation (49) or paired maternal and cord blood samples at delivery (50) have reported significant correlations between maternal and fetal/newborn concentrations of cortisol.…”
Section: Discussionmentioning
confidence: 99%
“…CRH is primarily expressed in human placenta and instead of the negative feedback loop cortisol-ACTH-CRH; there is a positive one between cortisol and CRH, while the ACTH production stagnates. CRH directly stimulates production of 5 steroid sulfates in the fetal zone of the fetal adrenal (FZ) [36,37] and cortisol synthesis in the transitional zone of the fetal adrenal (TZ) [38] via binding to ACTH receptors [39]. ACTH receptor mRNA is localized in all cortical zones but its abundance is higher in DZ (definitive zone) than in FZ [40].…”
Section: The Key Role Of Placental Crh In the Regulation Of Steroid Bmentioning
confidence: 99%